2013
DOI: 10.1093/icvts/ivt520
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, severity and perioperative risk factors for atrial fibrillation following pulmonary resection

Abstract: While the majority of PAF is uncomplicated and transient, one-third of cases lead to persistence or major intervention. Age, coronary artery disease and extent of surgery/stage increase the risk of PAF following pulmonary resection. Identifying patients with elevated risk may lead to targeted prophylaxis to reduce the incidence of PAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 24 publications
3
47
2
2
Order By: Relevance
“…314,318 Ivanovic et al 316 reported a similar incidence (11.8%) of a new documented postoperative AF that required pharmaco logical therapy among patients undergoing pulmonary resection (n=363). Patients with postoperative AF had a significantly longer mean length of stay (10.5 versus 6.9 days).…”
Section: Recommendationmentioning
confidence: 84%
See 3 more Smart Citations
“…314,318 Ivanovic et al 316 reported a similar incidence (11.8%) of a new documented postoperative AF that required pharmaco logical therapy among patients undergoing pulmonary resection (n=363). Patients with postoperative AF had a significantly longer mean length of stay (10.5 versus 6.9 days).…”
Section: Recommendationmentioning
confidence: 84%
“…In a consecutive sample of patients undergoing pulmo nary resection, the overall incidence of postoperative AF was 11.8%, with a quarter of patients experiencing AF in the first 24 hours; the incidence peaked at 2.5 days postoperatively. 316 Other investigators noted that AF develops most frequently 2 days after noncardiac thoracic surgery. 315,317 Thus, it is reasonable to recom mend electrocardiographic monitoring through postop erative day 2 to 3 for pulmonary resection, with longer periods determined by the clinician for those with mul tiple risk factors.…”
Section: Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…New-onset AF is a common arrhythmic complication of critical illness, with an incidence that varies from 4 to 9% in general intensive care unit patients, to 32 to 50% in patients after major cardiac and thoracic surgery. (1)(2) New-onset AF is associated with increased morbidity and mortality in patients hospitalized for heart failure, as well as various other critical conditions, although it is possible that AF in these cases is primarily a marker of disease severity rather than a direct cause of death. (3,4) AF is associated with cardioembolic events and heart failure, longer hospital stays, and reduced quality of life as well as a two to five-fold increased mortality.…”
Section: Introductionmentioning
confidence: 99%